1996
DOI: 10.1095/biolreprod54.1.264
|View full text |Cite
|
Sign up to set email alerts
|

Residence half-life of IgG administered topically to the mouse vagina

Abstract: Antibodies delivered directly to the vagina can provide passive immunoprotection against pregnancy and sexually transmitted disease. The duration of protection is limited by the residence time of the antibodies in the vagina; to our knowledge such residence times have not been reported. We investigated the time-course of disappearance of IgG delivered to the mouse vagina using three different methods to monitor the amount of administered IgG remaining in the vagina: gamma counting of 125I-IgG, viral neutraliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…It is possible, however, that technical limitations may have prevented us from detecting a protective effect. The concentration of antibodies may not have been high enough and similar to that reported by Sherwood et al [50], antibodies were gradually lost within 24 hrs post-inoculation. Clearance via opsonophagocytosis might not occur during this time frame since phagocytes are not detected in infected murine tissue until 2 to 5 days post-inoculation [38].…”
Section: Discussionsupporting
confidence: 76%
“…It is possible, however, that technical limitations may have prevented us from detecting a protective effect. The concentration of antibodies may not have been high enough and similar to that reported by Sherwood et al [50], antibodies were gradually lost within 24 hrs post-inoculation. Clearance via opsonophagocytosis might not occur during this time frame since phagocytes are not detected in infected murine tissue until 2 to 5 days post-inoculation [38].…”
Section: Discussionsupporting
confidence: 76%
“…The reliability of a murine model to predict the success of a gonorrhea vaccine in humans may be hindered by the absence of certain human-specific adherence receptors, such as the CD46 gonococcal pilus receptor [37] and the CD66 family of Opa protein receptors [38]. However, it is likely that gonococci do adhere to the vaginal mucosa in the model we describe, because their ability to exist for prolonged periods of time in this environment suggests that they have a mechanism to resist clearance by constant shedding of vaginal mucus [39]. Indeed, epithelial cell-associated gonococci were seen in stained smears from infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, intravaginal vaccination studies utilizing Toll-like receptor (TLR) agonists and CD4 + T helper epitopes [7] or powerful adjuvants such as cholera toxin [8] have demonstrated that immunization at this mucosal surface is possible but responses elicited to unadjuvanted vaccine antigens, where vaginal epithelial barrier integrity is maintained, have been modest [9,10]. This may be due to a number of reasons, distinct from the recruitment and activation of immune responsive cells, such as the inability of vaccinating antigens to traverse the type II stratified squamous epithelial barrier characteristic of the lower female reproductive tract [11], the possibility that the female reproductive tract is directed more towards an induced state of tolerance rather than inflammation [12], vaginal leakage of the applied antigen [13] or sequestration and elimination of the antigen by locally produced mucus and proteases [14,15]. For human immunodeficiency virus (HIV) there is the additional concern that vaccine/adjuvant-induced local inflammation may fuel infection through the recruitment of target cells as suggested by a recent clinical trial.…”
Section: Introductionmentioning
confidence: 99%